Practical stability for fractional impulsive control systems with noninstantaneous impulses on networks - You, Jin; Sun, Shurong (Nonlinear Analysis: Modelling and Control, 2022)
This paper investigates practical stability for a class of fractional-order impulsive control coupled systems with noninstantaneous impulses on networks. Using graph theory and Lyapunov method, new criteria for practical stability, uniform practical stability as well as practical asymptotic stability are established. In this paper, we extend graph theory to fractional-order system via piecewise Lyapunov-like functions in each vertex system to construct global Lyapunov-like functions. Our results are generalization of some known results of practical stability in the literature and provide a new method of impulsive control law for impulsive control systems with noninstantaneous impulses. Examples are given to illustrate the effectiveness of our results
Keywords: practical stability; fractional order; noninstantaneous impulses; networks; graph theory